Peripapillary pachychoroid syndrome, a different pathway in venous remodelling of the choroidal vasculature - Giuseppe Donvito; Vito Primavera (American Journal of Ophthalmology Case Reports)
Objective: Peripapillary pachychoroid syndrome (PPS) is a recently described syndrome belonging to the pachychoroid disease spectrum (PDS) group.Our aim is to demonstrate with PPS, the presence of a venous collateral circulation which joins the peripapillary choroidal venous system with the central retinal vein via the circulation of the prelaminar region.This collateral circulation reduces venous congestion of the nasal choroid secondary to outflow obstruction through the vortex veins or the choroidopial veins.It is also our intention to demonstrate with a retrospective analysis, the stages of development and possible spontaneous regression of the illness. Observation: We describe the clinical evolution of a patient affected by PPS over a 5-year period. Conclusion and importance: The increased outflow resistance via the vortex veins, as observed in patients affected by PDS, is the cause of congestion of the choroid and related chorioretinal manifestations.Vortex veins anastomosis in the watershed zones develops to compensate stasis.We believe that in the PPS cases we observed, and in each case of PPS, the increased venous choroidopial outflow resistance at the level of the nasal macular choroid determines the formation of a collateral circulation which develops between the peripapillary choroid and the central retinal vein, passing through the prelaminar region.Furthermore, this study highlights how stages of disease activity can quickly be followed by major structural changes in the outer retina.This suggests that treatment should not be delayed if the disease involves the central retina.